Finding patterns in spatial data using kernel-based clustering method - 448016 Mohd. Noor Md. Sap; A. Majid Awan; International Conference on Intelligent Knowledge System (2nd : 2005 : Istanbul, Turkey) (Skudai : Universiti Teknologi Malaysia, 2005)
41